2008
DOI: 10.3748/wjg.14.6154
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness in the hepatitis B virus carrier: A non-invasive marker of liver disease influenced by the pattern of transaminases

Abstract: AIM:To investigate the usefulness of transient elastography by Fibroscan (FS), a rapid non-invasive technique to evaluate liver fibrosis, in the management of chronic hepatitis B virus (HBV) carriers. METHODS: In 297 consecutive HBV carriers, we studied the correlation between liver stiffness (LS), stage of liver disease and other factors potentially influencing FS measurements. In 87 chronic hepatitis B (CHB) patients, we monitored the FS variations according to the spontaneous or treatment-induced variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
103
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 28 publications
16
103
4
1
Order By: Relevance
“…Some studies with transient elastography (19)(20)(21), SWE (21), and MR elastography (22,23) have concluded that the correlation between liver stiffness values and fibrosis stage is not affected by steatosis or necroinflammation. Other studies have suggested that inflammation, as suggested by elevated transaminase levels (24,25) or diagnosed at liver biopsy (26)(27)(28), affects transient elastography assessment of fibrosis. Similarly, steatosis has been reported to have no effect on acoustic radiation force imaging-based fibrosis assessment (29), whereas in several transient elastography studies, steatosis has been reported to have an effect on noninvasive fibrosis staging (28,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies with transient elastography (19)(20)(21), SWE (21), and MR elastography (22,23) have concluded that the correlation between liver stiffness values and fibrosis stage is not affected by steatosis or necroinflammation. Other studies have suggested that inflammation, as suggested by elevated transaminase levels (24,25) or diagnosed at liver biopsy (26)(27)(28), affects transient elastography assessment of fibrosis. Similarly, steatosis has been reported to have no effect on acoustic radiation force imaging-based fibrosis assessment (29), whereas in several transient elastography studies, steatosis has been reported to have an effect on noninvasive fibrosis staging (28,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…For staging fibrosis F≥2, F≥3 and F=4, the summary sensitivity was 0.81, 0.82 and 0.86, respectively, the summary specificity was 0.82, 0.87 and 0.87, respectively, and the corresponding AUROC was 0.88, 0.91 and 0.93, respectively (96). The cut-off values for significant fibrosis (≥F2) ranged from 5.8 to 8.8 kPa, for fibrosis ≥F3 from 7.0 to 13.5 kPa, and for cirrhosis (F4) from 9.0 to 16.9 kPa (97)(98)(99)(100)(101)(102)(103). A recent study showed the utility of TE for the diagnosis of fibrosis in 263 HBV patients with ALT levels <2× upper limit of normal (ULN), particularly in those with at least significant underlying fibrosis.…”
Section: Liver Stiffness Measurement: Transient Elastography (Te)-fibmentioning
confidence: 99%
“…Thus, we searched previous studies which focused on the performance of LSM in patients with CHB and identified four studies (2 from Europe and another 2 from Asia) in the literature. [17][18][19][20] Of these, one European study with Ishak system with six fibrosis grading which is different from four grading of Batts and Ludwig system was excluded 19,21 Although two Asian studies did not show complete cutoff LSM values for each fibrosis stage (missed cutoff value for ‡F2 fibrosis in one study 17 and missed value for ‡F3 in the other study, 20 we selected one of them with larger sample size (n = 161 vs. 88) as reference for comparison between Asian population. 17 Finally, the optimal cutoff LSM values for ‡F2, ‡F3 and F4 fibrosis stage of Chan et al were 6.0, 8.4 and 9.0 kPa respectively 17 and those of Marcellin et al were 7.2, 8.1 and 11.0 kPa respectively.…”
Section: Selection Of Reference Cutoff Lsm Valuesmentioning
confidence: 99%